2017
DOI: 10.1111/ijn.12606
|View full text |Cite
|
Sign up to set email alerts
|

Lesbian, gay, and bisexual (LGB) people's experiences of nursing health care: An emancipatory nursing practice integrative review

Abstract: Aim: To review current research on lesbian, gay, and bisexual (LGB) individuals' experience of nursing services from an emancipatory nursing practice framework.Background: As LGB issues are marginalized in health care, it is important to understand LGB

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 35 publications
0
11
0
2
Order By: Relevance
“…Moreover, 29% of LGB respondents reported that they believed they would be treated differently by medical personnel because of their LGB, transgender, or queer status (Human Rights Campaign Foundation, ). A review study of LGB individuals’ experiences with nursing services determined that LGB individuals experienced a nexus of exclusion and oppressive social norms (Nhamo‐Murire & Macleod, ). LGB individuals may be aware of the possibility of stigmatization and thus conceal their sexual orientation from health care providers or delay seeking care (Institute of Medicine, ; Whitehead, Shaver, & Stephenson, ; Willging, Salvador, & Kano, ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, 29% of LGB respondents reported that they believed they would be treated differently by medical personnel because of their LGB, transgender, or queer status (Human Rights Campaign Foundation, ). A review study of LGB individuals’ experiences with nursing services determined that LGB individuals experienced a nexus of exclusion and oppressive social norms (Nhamo‐Murire & Macleod, ). LGB individuals may be aware of the possibility of stigmatization and thus conceal their sexual orientation from health care providers or delay seeking care (Institute of Medicine, ; Whitehead, Shaver, & Stephenson, ; Willging, Salvador, & Kano, ).…”
Section: Introductionmentioning
confidence: 99%
“…Schroeder and DiAngelo (2010) point out that the persistent identification of nursing as a 'caring' profession inadvertently creates and maintains the discourse of colour blindness, as it maintains the idea that nurses treat everyone the same and do not oppress. Furthermore, it implies that nurses have evolved past influences of stigmatisation, ignorance and discrimination, a claim that is contradicted by several studies (see, e.g., Ben, Cormack, Harris, & Paradies, 2017;Fiscella & Sanders, 2016;Grant & Guerin, 2018;Lisy, Peters, Schofield, & Jefford, 2018;Nhamo-Murire & Macleod, 2017;Trollor et al, 2016). Norm-critical perspectives in education could add discussions about power and privilege to the seemingly neutral and morally righteous ideal of nursing seen in our analysis, identifying that there are no objective outlooks on caring.…”
Section: Discussionmentioning
confidence: 66%
“…When we interact with colleagues and patients, we do so from the perspective of our membership of particular social groups. In meeting people from other social groups who are different from us, there is the possibility of drawing on stereotypes that are culturally available as way of framing our interactions (Kunda 1999). This can lead to interactions which are based on assumptions and possibly prejudice about people belonging to particular social groups.…”
Section: Diversity Power and Identitymentioning
confidence: 99%
“…Prejudice is when we value a person negatively because of their perceived membership of a particular social group (Kunda 1999). Neuroscientific evidence suggests that even those without apparent prejudice can experience activation of negative stereotypes in some contexts (Forbes et al 2012;Kunda 1999). This suggests that there is potential for anyone to act in a prejudiced way.…”
Section: Endmentioning
confidence: 99%